Kinematic analysis of men bobsled push starts - Smith, S. L.; Kivi, D. M. R.; Camus, H.; Pickels, R.; Sands, W. A. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study was to provide a descriptive analysis of selected kinematic variables associated with the push start for brakemen in the two-man bobsled. Eleven male bobsledders served as subjects for this study. The subjects were videotaped at 120 Hz during competition at the Lake Placid, NY bobsled track as they were competing for positions on the mens 2004 National Bobsled Team. Selected groups of variables measured at specific events in this study included step length, frequency, and foot contact time; COM velocity; and trunk, knee, and elbow angles. A relationship of 0.63 was determined between start time and finish time; an exploratory correlational analysis between start time and COM velocity at 2nd step take-off (TO) was -0.63. Start time is of critical importance in determining final race time.